Immune-based Therapeutics for Pediatric Cancer - Capitini, Christian M. (2010)
IMPORTANCE TO THE FIELD: Although most children with cancer are cured, there remain significant limitations of standard treatment, most notably chemotherapy resistance and non-specific toxicities. Novel immune-based therapies that target pediatric malignancies offer attractive adjuncts and/or alternatives to commonly employed cytotoxic regimens of chemotherapy or radiotherapy. Elucidation of the principles of tumor biology and the development of novel laboratory technologies over the last decade have led to substantial progress in bringing immunotherapies to the bedside. AREAS COVERED IN THE REVIEW: Current immunotherapeutic clinical trials in pediatric oncology and the science behind their development are reviewed. WHAT THE READER WILL GAIN: Most of the immune-based therapies studied to date have been well tolerated, and some have shown promise in the setting of refractory or high-risk malignancies, demonstrating that immunotherapy has the potential to overcome resistance to conventional chemotherapy. TAKE HOME MESSAGE: Some immune-based therapies, such as ch14.18 and MTP-PE, have already been proven effective in phase III randomized trials. Further studies are needed to optimize and integrate these therapies into standard regimens, and to test them in randomized trials for patients with childhood cancer.